Coherent Beam Combining of Fiber Amplifiers Using Stochastic Parallel Gradient Descent Algorithm and Its Application - Zhou, Pu; Liu, Zejin; Wang, Xiaolin; Ma, Yanxing; Ma, Haotong; Xu, Xiaojun; Guo, Shaofeng (IEEE journal of selected topics in quantum electronics, 2009)
We present theoretical and experimental research on coherent beam combining of fiber amplifiers using stochastic parallel gradient descent (SPGD) algorithm. The feasibility of coherent beam combining using SPGD algorithm is detailed analytically. Numerical simulation is accomplished to explore the scaling potential to higher number of laser beams. Experimental investigation on coherent beam combining of two and three W-level fiber amplifiers is demonstrated. Several application fields, i.e., atmosphere distortion compensating, beam steering, and beam shaping based on coherent beam combining using SPGD algorithm are proposed.